Evaluating Signage Accessibility for Individuals with Visual Impairments: A Case Study in Ecuador - Arias Flores, Hugo Patricio; Valencia-Aragón, Kevin; Sandra Sanchez-Gordon; Tania Calle-Jimenez (My University, 2024)
A signage system is a visual design consisting of identification, guidance, explanation, warning, and other functions through a combination of text, graphics, and color that facilitates the orientation and movement of occupants in buildings by representing explicit information about the configuration and overall structure of the building. In this sense, well-placed signage provides information and significantly influences the search for paths in public spaces, but not all of these spaces meet the conditions of accessibility and inclusion. From this perspective, the general objective of this research is to identify, analyze, and evaluate the shortcomings of signage for individuals with visual impairments based on the requirements and legal regulations in Ecuador. The methodology was based on collecting photographs of signage located in a higher education institution. These photographs were selected in a way that they encompass the most important characteristics of informative signage. The results show that 44.44% comply with the current regulations in Ecuador, and 66.66% comply with the regulations for the inclusion of individuals with low vision. In the future, it is considered to propose a signage system that incorporates technology.
Keywords: accessibility; public spaces; regulations for the inclusion; signage system; visual impairments